Community Agriculture Management in the Gayo Highlands: Integration of Customary and Local Government Authorities - Latif, Ikhwan Rahmatika; Saputra, Ilham Mirza; Ikhsan, Ikhsan; Hajad, Vellayati (Jurnal Administrasi dan Kebijakan Publik, 2024)
The research focuses on addressing the challenges associated concerning agricultural management in the Gayo Highlands community, specifically in the Aceh Tengah Regency. Both local village authorities and customary institutions are responsible for the use of the agricultural area. The main objective is to foster a collaborative and effective approach between these two entities, thus minimizing any potential overlap of responsibilities. The research aims to identify prudent measures that can be taken to enhance agricultural practices within the Gayo Highlands community while considering the influence and existence of both institutions within the broader framework of Aceh governance. A qualitative research methodology is employed, consisting of preliminary observations and analysis of authority structures. The researchers then suggested the implementation of wise policies to ensure sustainable agricultural management. Ultimately, the research endeavours to improve the quality of life for the Gayo Highlands community by establishing a solid foundation for agricultural development without disregarding the authorities of traditional and village governance